- #1

- 194

- 0

## Main Question or Discussion Point

I did the following:

dy/(y^2 -4 ) = dx

Integral ( -1/4 /y + 2 + 1/4 / ( y-2) . dy = Integral dx

-1/4 ln | y + 2 | + 1 /4 ln |y -2 | + C = x

Multiplying all thru by - 4 we get

ln | y + 2 | + ln | y - 2 | + 4C = 4x ( Note: 4C is another 'C'which is a bigger C)

ln | y + 2 / y - 2| + C = 4x

C = 4x - ln | y + 2 / y -2 |

If this is correct, can we simplify the solution any further.

dy/(y^2 -4 ) = dx

Integral ( -1/4 /y + 2 + 1/4 / ( y-2) . dy = Integral dx

-1/4 ln | y + 2 | + 1 /4 ln |y -2 | + C = x

Multiplying all thru by - 4 we get

ln | y + 2 | + ln | y - 2 | + 4C = 4x ( Note: 4C is another 'C'which is a bigger C)

ln | y + 2 / y - 2| + C = 4x

C = 4x - ln | y + 2 / y -2 |

If this is correct, can we simplify the solution any further.